ZrO2 / Ti4O7-Al2O3 / C composite nanofiber material as well as preparation method and application thereof

By introducing ZrO2/Ti4O7-Al2O3/C composite nanofiber material into the negative electrode material of lithium metal battery, the problems of lithium dendrites are solved and the cycle life and rate performance of the battery are improved.

CN119685974AActive Publication Date: 2025-03-25SHAANXI UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411746873.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-25
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

There are problems in lithium dendrites growing and volume expansion in lithium metal batteries, resulting in poor cycle life and rate performance of the battery, and traditional carbon-based materials have interfacial lithium sparse problems.

Method used

ZrO2/Ti4O7-Al2O3/C composite nanofiber material is used as the negative electrode material of lithium metal battery. Through electrospinning method combined with high-temperature carbonization strategy, lithium-philic Ti, Zr, and C elements are introduced on the surface of the three-dimensional Al2O3 main body.

Benefits of technology

It effectively inhibits the growth and volume expansion of lithium metal negative electrode dendrites, improves the cycle life and rate performance of the battery, and improves the lithium-philicity of the carbon substrate and reduces the lithium nucleation potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685974A_ABST
    Figure CN119685974A_ABST
Patent Text Reader

Abstract

The invention discloses a ZrO2 / Ti4O7-Al2O3 / C composite nanofiber material and a preparation method and application thereof.The preparation method comprises the steps that an aluminum oxide nanorod is prepared and modified through sodium hydroxide, lithium-loving Ti and Zr elements are introduced to the surface of the aluminum oxide nanorod subjected to surface modification through an electrostatic spinning method, stable ZrO2 / Ti4O7-Al2O3 composite nanofiber fabric is formed, and the ZrO2 / Ti4O7-Al2O3 composite nanofiber fabric is prepared. The ZrO2 / Ti4O7-Al2O3 / C composite nanofiber material is obtained by covering with graphite foil and performing high-temperature carbonization, and is used as a lithium metal battery negative electrode material, so that dendritic crystal growth and volume expansion of a lithium metal negative electrode are effectively inhibited, the cycle life of the battery is prolonged, and the rate capability of the battery is improved; the ZrO2 / Ti4O7-Al2O3 / C composite nanofiber negative electrode is assembled into a half battery, so that dendritic crystal growth of the lithium metal negative electrode is effectively inhibited, the cycle life of the battery is prolonged, and the rate capability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials, and relates to a lithium metal battery electrode material, and specifically relates to a ZrO 2 / Ti 4 O 7 -Al 2 O 3 / C composite nanofiber material and its preparation method and application. Background Art

[0002] With the rapid development of society and the continuous growth of global energy demand, the application of new energy vehicles, artificial intelligence equipment, smart energy storage grids, etc. has made the whole society's demand for high energy density, long life and sustainable batteries increasingly urgent, especially in the fields of renewable energy and electric vehicles. Among various battery technologies, lithium metal batteries are favored by people for their advantages such as excellent theoretical capacity and low potential. However, in practical applications, lithium metal batteries still have some obstacles to overcome, such as solid electrolyte interface (SEI) instability and increased electrolyte consumption, which are usually caused by the growth of lithium dendrites.

[0003] In order to overcome these problems, researchers are actively exploring various methods, such as electrolyte modification, functionalized separator modification and structured negative electrode design, to inhibit the growth and volume expansion of lithium dendrites. Among them, by designing the lithium negative electrode structure using a three-dimensional carbon-based lithium-philic current collector, the problems of lithium dendrite growth and volume expansion in lithium metal batteries can be effectively overcome. However, traditional carbon-based materials have interfacial lithium repellency problems, which may hinder lithium nucleation and cause lithium metal agglomeration. Although precious metal nanoparticles, doping with other elements and other traditional alloys can improve the lithium affinity of electrodes, they are usually accompanied by additional side effects and high costs, which limit their widespread application. In addition, traditional carbon-based materials may have interfacial lithium repellency problems in lithium metal batteries, resulting in lithium agglomeration and uneven distribution, which in turn affects battery performance and life. Therefore, in response to the interfacial lithium repellency problem of carbon-based materials, researchers are actively developing new three-dimensional carbon-based lithium-philic current collector structures to solve the various challenges of lithium metal batteries during use. In recent years, nanocomposite fiber materials have attracted much attention as an emerging technology. With metal and ceramic matrices as the continuous phase, other inorganic particles containing different elements are dispersed in the matrix material through appropriate preparation methods. By combining different elements, unlimited combinations can meet the required performance and achieve coordination between multiple components. Therefore, the study of composite nanofiber lithium-free negative electrode materials has become an important direction for solving the problem of lithium metal batteries. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention aims to provide a ZrO 2 / Ti4 O 7 -Al 2 O 3 / C composite nanofiber material and its preparation method and application, introducing materials containing Ti, Zr, and C into Al 2 O 3 The three-dimensional skeleton surface is used as the negative electrode material of lithium metal batteries, which effectively inhibits the growth of lithium metal negative electrode dendrites and improves the cycle life and rate performance of the battery.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A ZrO 2 / Ti 4 O 7 -Al 2 O 3 The preparation method of the / C composite nanofiber material comprises the following steps:

[0007] Step 1, add 5-10g of aluminum isopropoxide to 10-30ml of water and stir until evenly dispersed, then add 5-15ml of acetic acid and continue stirring until the solution is clear, freeze-dry and grind to obtain aluminum oxide nanorod powder;

[0008] Step 2: Disperse 150-300 mg of aluminum oxide nanorod powder in 20-40 ml of deionized water, then add 75-120 ml of a 2 mol / L sodium hydroxide aqueous solution to the mixture of the aluminum oxide nanorod powder and deionized water under stirring, continue stirring until uniform, collect the surface-modified aluminum oxide nanorods by centrifugation, and then centrifugally wash, dry, and grind to obtain the surface-modified aluminum oxide nanorods;

[0009] Step 3: ultrasonically disperse 100-150 mg of the surface-modified alumina nanorods prepared in step 2 in 5-15 g of an acetic acid and ethanol mixed solution, then add 0.2-1 g of polyvinyl pyrrolidone and stir at 40-60 ° C for 5-12 h, then add 1-10 g of tetraisopropyl titanate in an ice water bath and stir evenly, then add 0.2-1 g of zirconium acetate and stir evenly to obtain an electrospinning suspension, and spin, weave, and stabilize the suspension in a vacuum oven to form a stable ZrO 2 / Ti 4 O 7 -Al 2 O 3 Composite nanofiber fabric;

[0010] Step 4: ZrO 2 / Ti 4 O 7 -Al 2 O 3The composite nanofiber fabric was cut into strips of 150 mm in length and 30 mm in width, each of which was covered with graphite foil and stacked on a square crucible. 2 In the atmosphere, heat to 500-1500℃ and keep for 0.5-3h, then cool naturally to room temperature, take out the sample, and obtain the high temperature carbonized ZrO 2 / Ti 4 O 7 -Al 2 O 3 / C composite nanofiber materials.

[0011] The present invention also has the following technical features:

[0012] Preferably, the grinding in step 1 and step 2 is performed using a mortar for 20 to 30 minutes.

[0013] Preferably, the drying in step 2 is carried out in an oven at 80-100° C. for 8-12 hours.

[0014] Preferably, the mass ratio of acetic acid to ethanol in the acetic acid-ethanol mixed solution described in step three is 2:3.

[0015] Preferably, the parameters of the spinning in step 3 are: the distance between the current collector and the stainless steel needle is 18 cm, the voltage, feed rate and distance are fixed at 25 kV and 1 mL / h respectively, and the humidity is 40% to 60%.

[0016] Preferably, in step 3, ZrO 2 / Ti 4 O 7 -Al 2 O 3 The stable temperature of the composite nanofiber fabric in the vacuum oven is set to 70-80°C for 8-10 hours.

[0017] The present invention also protects a ZrO prepared by the method as described above. 2 / Ti 4 O 7 -Al 2 O 3 / C composite nanofiber materials and their applications in lithium metal battery anodes.

[0018] Compared with the prior art, the present invention has the following technical effects:

[0019] The present invention combines electrospinning with high temperature carbonization strategy to form a three-dimensional Al 2 O 3 The lithium-philic elements Ti, Zr, and C are introduced into the main surface. 2 O 3The fiber rod framework can reduce the local current density and slow down the volume expansion of lithium metal. The introduction of Ti, Zr and C elements improves the lithium affinity of the carbon substrate and reduces the nucleation potential of lithium. It is used as the negative electrode material of lithium metal batteries, effectively inhibits the growth and volume expansion of lithium metal negative electrode dendrites, and improves the cycle life and rate performance of the battery. 2 / Ti 4 O 7 -Al 2 O 3 The / C composite nanofiber anode was assembled into a half-cell at a current density of 2 mA cm -2 , with a specific capacity of 1 mAh cm -2 When the electrode stability was tested, the average coulomb efficiency value was 98% after 170 stable cycles; in addition, the ZrO 2 / Ti 4 O 7 -Al 2 O 3 The initial capacity of the anode-free HEA / CF||NCM811 full cell at 1C is 113.2 mAh g -1 After 160 cycles, it still has 19 mAh g -1 , the CE was stably maintained at around 95.2% during the cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 / C composite nanofiber lithium-free negative electrode material folding resistance test flow chart;

[0021] Figure 2 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 SEM image of / C composite nanofiber lithium-free anode material;

[0022] Figure 3 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 EDS image of / C composite nanofiber lithium-free anode material;

[0023] Figure 4 The ZrO prepared in Example 1 2 / Ti4 O 7 -Al 2 O 3 XRD pattern of / C composite nanofiber lithium-free anode material;

[0024] Figure 5 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 Electrochemical performance diagram of / C composite nanofiber lithium-free negative electrode material;

[0025] Figure 6 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 Overpotential diagram of / C composite nanofiber lithium-free anode material;

[0026] Figure 7 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 Full cell impedance diagram of / C composite nanofiber lithium-free anode material;

[0027] Figure 8 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 DRT diagram of half-cell of / C composite nanofiber lithium-free anode material;

[0028] Fig. 9 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 Performance diagram of a full battery with / C composite nanofiber lithium-free anode material at a current of 1C. DETAILED DESCRIPTION

[0029] The present invention is specifically described below in conjunction with the accompanying drawings and Examples, but the embodiments of the present invention are not limited thereto. The reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods for which specific experimental conditions are not indicated in the following examples are usually in accordance with conventional experimental conditions. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.

[0030] Example 1

[0031] This embodiment provides a ZrO 2 / Ti 4 O 7 -Al 2 O 3 The preparation method of the / C composite nanofiber material specifically comprises the following steps:

[0032] Step 1: add 5 g of aluminum isopropoxide to 18 ml of water and stir until evenly dispersed, then add 9 ml of acetic acid and continue stirring until the solution is clear, freeze-dry and grind in a mortar for 30 min to obtain aluminum oxide nanorod powder;

[0033] Step 2: 150 mg of alumina nanorod powder was dispersed in 30 ml of deionized water, and then 100 ml of 2 mol / L sodium hydroxide aqueous solution was added to the mixture of the alumina nanorod powder and deionized water under stirring, and the mixture was stirred for 5 min until uniform, and then the surface-modified alumina nanorods were collected by centrifugation, and then further dispersed in 30 ml of deionized water, and then the solid was collected by centrifugation, dried in an oven at 80° C. for 10 h, and ground in a mortar for 30 min to obtain the surface-modified alumina nanorods;

[0034] Step 3: ultrasonically disperse 100 mg of the surface-modified alumina nanorods prepared in step 2 in 11 g of an acetic acid and ethanol mixed solution, wherein the mass ratio of acetic acid to ethanol in the acetic acid and ethanol mixed solution is 2:3; then add 0.4 g of polyvinyl pyrrolidone and stir at 40 ° C for 10 h, then add 3 g of tetraisopropyl titanate in an ice water bath and stir evenly, then add 0.7 g of zirconium acetate and stir for 10 min until uniform electrospinning suspension is obtained, and the mixed suspension is loaded into a 20 ml syringe, and the distance between the collector and the stainless steel needle is set to 18 cm, and the voltage, feed rate and distance are fixed at 25 kV and 1 mL / h, respectively, and the humidity is controlled at 40% for electrospinning; after spinning, zirconium oxide / titanium suboxide-alumina (ZrO 2 / Ti 4 O 7 -Al 2 O 3 ) composite nanofibers are separated from the release paper; finally, zirconium oxide / titanium suboxide-aluminum oxide (ZrO 2 / Ti 4 O 7 -Al 2 O 3 ) The composite nanofibers were stabilized in a vacuum oven, the stable temperature was set at 70 °C, the time was 8 h, and a stable ZrO 2 / Ti 4 O 7 -Al 2O 3 Composite nanofiber fabric;

[0035] Step 4: ZrO 2 / Ti 4 O 7 -Al 2 O 3 The composite nanofiber fabric was cut into strips of 150 mm in length and 30 mm in width, each of which was covered with graphite foil and stacked on a square crucible. After loading and sealing the tube furnace test tube, the tube furnace was heated in N 2 The sample was heated to 1000℃ and kept for 1h under the atmosphere, and then cooled to room temperature naturally. The sample was taken out to obtain the ZrO 2 / Ti 4 O 7 -Al 2 O 3 / C composite nanofiber lithium-free anode material;

[0036] During heating, a slow heating rate of 1K / min is used in the section from room temperature to 100°C to remove oxygen contamination; a faster heating rate of 2K / min is used in the section from 100°C to 300°C and from 700°C to 1000°C; in the section from 300°C to 700°C, the heating rate is 1K / min.

[0037] The following tests were performed on the sample properties:

[0038] 1. Folding resistance and high temperature resistance

[0039] Figure 1 The above is ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 Folding resistance test flow chart of C / C composite nanofiber lithium-free negative electrode materials. From the flow chart, we can observe that ZrO 2 / Ti 4 O 7 -Al 2 O 3 / C composite nanofiber negative electrode material has good folding resistance;

[0040] Figure 1 The following is the ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 / C composite nanofiber lithium-free negative electrode material high temperature resistance test flow chart; from the flow chart, it can be observed that ZrO 2 / Ti 4 O 7 -Al2 O 3 / C composite nanofiber lithium-free negative electrode material has good high temperature resistance.

[0041] 2 Morphology

[0042] Figure 2 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 SEM image of / C composite nanofiber lithium-free negative electrode material. From the SEM image, we can observe ZrO 2 / Ti 4 O 7 -Al 2 O 3 / C composite nanofibers present a three-dimensional network structure.

[0043] Figure 3 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 EDS image of / C composite nanofiber lithium-free negative electrode material, from Figure 3 It can be seen that Ti, Zr, and C are 2 O 3 Evenly distributed in the fibers.

[0044] 3. Composition

[0045] Figure 4 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 XRD pattern of / C composite nanofiber lithium-free negative electrode material, such as Figure 4 As shown, the three diffraction peaks of the X-ray diffraction (XRD) of the material correspond to the (111), (200) and (1-20) planes of the FCC phase, respectively.

[0046] 4 Electrochemical performance

[0047] Figure 5 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 Electrochemical performance diagram of / C composite nanofiber lithium-free negative electrode material; Figure 5 As shown in the figure, the negative electrode prepared in the embodiment is assembled into a half-cell and the current density is 2 mA cm-2 , with a specific capacity of 1 mAh cm -2 The electrode stability was tested, with an average Coulombic efficiency value of 98% after 170 stable cycles.

[0048] Figure 6 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 Overpotential performance diagram of / C composite nanofiber lithium-free negative electrode material.

[0049] Figure 7 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 / C composite nanofiber lithium-free negative electrode material full battery impedance diagram; Figure 7 As shown, a full battery based on the negative electrode prepared in Example 1 and the NCM-811 positive electrode was assembled.

[0050] Figure 8 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 DRT diagram of half-cell of / C composite nanofiber lithium-free negative electrode material; Figure 8 As shown in the figure, DRT successfully distributes the electrochemical reaction process of lithium ions in the half-cell and the change of impedance with the increase / decrease of lithium content. It can be determined that ZrO 2 / Ti 4 O 7 -Al 2 O 3 / C negative electrode shows obvious and stable electrochemical processes in the four main peaks of 10-4~10-2 (D1), 10-2~10-1 (D2), 10-1~1 (D3) and 1~100s (D4), which correspond to: lithium ion transmission process, SEI film formation and penetration of SEI film process, lithium ion electronic reduction process and lithium metal diffusion process respectively.

[0051] Fig. 9 The ZrO prepared in Example 1 2 / Ti 4 O 7 -Al 2 O 3 Performance diagram of a full battery with / C composite nanofiber lithium-free negative electrode material at a current of 1C; Fig. 9As shown, the initial capacity of the full battery at 1C is 113.2 mAh g -1 After 160 cycles, it still has 19 mAh g -1 , the CE was stably maintained at around 95.2% during the cycle.

[0052] Example 2

[0053] This embodiment provides a ZrO 2 / Ti 4 O 7 -Al 2 O 3 The preparation method of / C composite nanofiber material specifically comprises the following steps:

[0054] Step 1: add 7 g of aluminum isopropoxide to 10 ml of water and stir until evenly dispersed, then add 5 ml of acetic acid and continue stirring until the solution is clear, freeze-dry and grind in a mortar for 20 min to obtain aluminum oxide nanorod powder;

[0055] Step 2: Disperse 200 mg of alumina nanorod powder in 20 ml of deionized water, then add 120 ml of a 2 mol / L sodium hydroxide aqueous solution to the mixture of the alumina nanorod powder and deionized water under stirring, continue stirring for 5 min until uniform, collect the surface-modified alumina nanorods by centrifugation, further disperse in 30 ml of deionized water, collect the solid by centrifugation, dry in an oven at 100 ° C for 8 h, and grind in a mortar for 20 min to obtain the surface-modified alumina nanorods;

[0056] Step 3: ultrasonically disperse 120 mg of the surface-modified alumina nanorods prepared in step 2 in 5 g of an acetic acid and ethanol mixed solution, wherein the mass ratio of acetic acid to ethanol in the acetic acid and ethanol mixed solution is 2:3; then add 0.2 g of polyvinyl pyrrolidone and stir at 50 ° C for 5 h, then add 1 g of tetraisopropyl titanate in an ice water bath and stir evenly, then add 0.2 g of zirconium acetate and stir for 10 min until uniform electrospinning suspension is obtained, and the mixed suspension is loaded into a 20 ml syringe, and the distance between the collector and the stainless steel needle is set to 18 cm, and the voltage, feed rate and distance are fixed at 25 kV and 1 mL / h, respectively, and the humidity is controlled at 50% for electrospinning; after spinning, zirconium oxide / titanium suboxide-alumina (ZrO 2 / Ti 4 O 7 -Al 2 O 3 ) composite nanofibers are separated from the release paper; finally, zirconium oxide / titanium suboxide-aluminum oxide (ZrO 2 / Ti 4 O 7 -Al 2 O3 ) The composite nanofibers were stabilized in a vacuum oven, the stable temperature was set at 80 °C, the time was 9 h, and a stable ZrO 2 / Ti 4 O 7 -Al 2 O 3 Composite nanofiber fabric;

[0057] Step 4: ZrO 2 / Ti 4 O 7 -Al 2 O 3 The composite nanofiber fabric was cut into strips of 150 mm in length and 30 mm in width, each of which was covered with graphite foil and stacked on a square crucible. After loading and sealing the tube furnace test tube, the tube furnace was heated in N 2 The sample was heated to 500 °C and maintained for 3 h under the atmosphere, and then cooled to room temperature naturally. The sample was taken out to obtain the high-temperature carbonized ZrO 2 / Ti 4 O 7 -Al 2 O 3 / C composite nanofiber lithium-free anode material.

[0058] Example 3

[0059] This embodiment provides a ZrO 2 / Ti 4 O 7 -Al 2 O 3 The preparation method of / C composite nanofiber material specifically comprises the following steps:

[0060] Step 1: add 10 g of aluminum isopropoxide to 38 ml of water and stir until evenly dispersed, then add 15 ml of acetic acid and continue stirring until the solution is clear, freeze-dry and grind in a mortar for 25 min to obtain aluminum oxide nanorod powder;

[0061] Step 2: 300 mg of alumina nanorod powder was dispersed in 40 ml of deionized water, and then 75 ml of 2 mol / L sodium hydroxide aqueous solution was added to the mixture of the alumina nanorod powder and deionized water under stirring, and the mixture was stirred for 5 min until uniform, and then the surface-modified alumina nanorods were collected by centrifugation, and then further dispersed in 30 ml of deionized water, and then the solid was collected by centrifugation, dried in an oven at 90 ° C for 12 h, and ground in a mortar for 25 min to obtain the surface-modified alumina nanorods;

[0062] Step 3: ultrasonically disperse 150 mg of the surface-modified alumina nanorods prepared in step 2 in 15 g of an acetic acid and ethanol mixed solution, wherein the mass ratio of acetic acid to ethanol in the acetic acid and ethanol mixed solution is 2:3; then add 1 g of polyvinyl pyrrolidone and stir at 60 ° C for 12 h, then add 10 g of tetraisopropyl titanate in an ice water bath and stir evenly, then add 1 g of zirconium acetate and stir for 10 min until uniform electrospinning suspension is obtained, and the mixed suspension is loaded into a 20 ml syringe, and the distance between the collector and the stainless steel needle is set to 18 cm, and the voltage, feed rate and distance are fixed at 25 kV and 1 mL / h, respectively, and the humidity is controlled at 60% for electrospinning; after spinning, zirconium oxide / titanium suboxide-alumina (ZrO 2 / Ti 4 O 7 -Al 2 O 3 ) composite nanofibers are separated from the release paper; finally, zirconium oxide / titanium suboxide-aluminum oxide (ZrO 2 / Ti 4 O 7 -Al 2 O 3 ) The composite nanofibers were stabilized in a vacuum oven at a temperature of 75 °C for 10 h to form a stable ZrO 2 / Ti 4 O 7 -Al 2 O 3 Composite nanofiber fabric;

[0063] Step 4: ZrO 2 / Ti 4 O 7 -Al 2 O 3 The composite nanofiber fabric was cut into strips of 150 mm in length and 30 mm in width, each of which was covered with graphite foil and stacked on a square crucible. After loading and sealing the tube furnace test tube, the tube furnace was heated in N 2 The sample was heated to 1500℃ and kept for 0.5h under the atmosphere, and then cooled to room temperature naturally. The sample was taken out to obtain the ZrO 2 / Ti 4 O 7 -Al 2 O 3 / C composite nanofiber lithium-free anode material.

[0064] Example 4

[0065] This embodiment provides a ZrO 2 / Ti 4 O 7 -Al 2 O 3The preparation method of the / C composite nanofiber material specifically comprises the following steps:

[0066] Step 1: add 6 g of aluminum isopropoxide to 18 ml of water and stir until evenly dispersed, then add 9 ml of acetic acid and continue stirring until the solution is clear, freeze-dry and grind in a mortar for 30 minutes to obtain aluminum oxide nanorod powder;

[0067] Step 2: Disperse 200 mg of alumina nanorod powder in 30 ml of deionized water, then add 100 mL of 2 mol / L sodium hydroxide aqueous solution to the mixture of alumina nanorod powder and deionized water under stirring, continue stirring for 5 minutes until uniform, collect the surface-modified alumina nanorods by centrifugation, further disperse in 30 ml of deionized water, collect the solid by centrifugation, dry in an oven at 80° C. for 10 hours, and grind in a mortar for 30 minutes to obtain the surface-modified alumina nanorods;

[0068] Step 3: ultrasonically disperse 100 mg of the surface-modified alumina nanorods prepared in step 2 in 11 g of an acetic acid and ethanol mixed solution, wherein the mass ratio of acetic acid to ethanol in the acetic acid and ethanol mixed solution is 2:3; then add 0.6 g of polyvinyl pyrrolidone and stir at 40 ° C for 10 h, then add 5 g of tetraisopropyl titanate in an ice water bath and stir evenly, then add 0.5 g of zirconium acetate and stir for 10 min until uniform electrospinning suspension is obtained, and the mixed suspension is loaded into a 20 ml syringe, and the distance between the collector and the stainless steel needle is set to 18 cm, and the voltage, feed rate and distance are fixed at 25 kV and 1 mL / h, respectively, and the humidity is controlled at 40% for electrospinning; after spinning, zirconium oxide / titanium suboxide-alumina (ZrO 2 / Ti 4 O 7 -Al 2 O 3 ) composite nanofibers are separated from the release paper; finally, zirconium oxide / titanium suboxide-aluminum oxide (ZrO 2 / Ti 4 O 7 -Al 2 O 3 ) The composite nanofibers were stabilized in a vacuum oven, the stable temperature was set at 70 °C, the time was 8 h, and a stable ZrO 2 / Ti 4 O 7 -Al 2 O 3 Composite nanofiber fabric;

[0069] Step 4: ZrO 2 / Ti 4 O 7 -Al 2 O3 The composite nanofiber fabric was cut into strips of 150 mm in length and 30 mm in width, each of which was covered with graphite foil and stacked on a square crucible. After loading and sealing the tube furnace test tube, the tube furnace was heated in N 2 The sample was heated to 1200℃ and kept for 1h under the atmosphere, and then cooled to room temperature naturally. The sample was taken out to obtain the ZrO 2 / Ti 4 O 7 -Al 2 O 3 / C composite nanofiber lithium-free anode material.

[0070] It should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it; without departing from the concept of the present invention, the deduction or replacement made by those skilled in the art shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a ZrO2 / Ti4O7-Al2O3 / C composite nanofiber material, characterized in that: The following steps are involved: Step 1, add 5-10g of aluminum isopropoxide to 10-30ml of water and stir until evenly dispersed, then add 5-15ml of acetic acid and continue stirring until the solution is clear, freeze-dry and grind to obtain aluminum oxide nanorod powder; Step 2: Disperse 150-300 mg of aluminum oxide nanorod powder in 20-40 ml of deionized water, then add 75-120 ml of a 2 mol / L sodium hydroxide aqueous solution to the mixture of the aluminum oxide nanorod powder and deionized water under stirring, continue stirring until uniform, collect the surface-modified aluminum oxide nanorods by centrifugation, and then centrifugally wash, dry, and grind to obtain the surface-modified aluminum oxide nanorods; Step 3, ultrasonically dispersing 100-150 mg of the surface-modified alumina nanorods prepared in step 2 in 5-15 g of an acetic acid and ethanol mixed solution, then adding 0.2-1 g of polyvinyl pyrrolidone and stirring at 40-60° C. for 5-12 h, then adding 1-10 g of tetraisopropyl titanate in an ice water bath and stirring evenly, then adding 0.2-1 g of zirconium acetate and stirring evenly to obtain an electrospinning suspension, spinning and weaving the suspension, and stabilizing it in a vacuum oven to form a stable ZrO2 / Ti4O7-Al2O3 composite nanofiber fabric; Step 4: Cut the ZrO2 / Ti4O7-Al2O3 composite nanofiber fabric into strips of 150 mm in length and 30 mm in width. Each strip is covered with graphite foil and stacked on a square crucible. In a N2 atmosphere, heat it to 500-1500°C and keep it for 0.5-3 h. After cooling it naturally to room temperature, take out the sample to obtain the ZrO2 / Ti4O7-Al2O3 / C composite nanofiber material after high-temperature carbonization.

2. The method for preparing the ZrO2 / Ti4O7-Al2O3 / C composite nanofiber material according to claim 1, characterized in that: The grinding described in step 1 and step 2 is performed using a mortar for 20 to 30 minutes.

3. The method for preparing the ZrO2 / Ti4O7-Al2O3 / C composite nanofiber material according to claim 1, characterized in that: The drying described in step 2 is drying in an oven at 80-100° C. for 8-12 hours.

4. The method for preparing the ZrO2 / Ti4O7-Al2O3 / C composite nanofiber material according to claim 1, characterized in that: The mass ratio of acetic acid to ethanol in the acetic acid-ethanol mixed solution described in step 3 is 2:

3.

5. The method for preparing the ZrO2 / Ti4O7-Al2O3 / C composite nanofiber material according to claim 1, characterized in that: The spinning parameters described in step 3 are as follows: the distance between the current collector and the stainless steel needle is 18 cm, the voltage, feed rate and distance are fixed at 25 kV and 1 mL / h respectively, and the humidity is 40% to 60%.

6. The method for preparing the ZrO2 / Ti4O7-Al2O3 / C composite nanofiber material according to claim 1, characterized in that: In step 3, the temperature of the ZrO2 / Ti4O7-Al2O3 composite nanofiber fabric in the vacuum oven is set to be stable at 70-80°C for 8-10 hours.

7. A ZrO2 / Ti4O7-Al2O3 / C composite nanofiber material prepared by the method according to any one of claims 1 to 6.

8. Use of the ZrO2 / Ti4O7-Al2O3 / C composite nanofiber material as claimed in claim 7 in a negative electrode of a lithium metal battery.

Citation Information

Patent Citations

  • C / Ti4O7 composite nanofiber based lithium-sulfur battery positive electrode material and preparation method therefor

    CN105489863A

  • Preparation method of high-performance gel polymer electrolyte and lithium ion battery

    CN113517468A

  • Solid oxide fuel cell connector coating and preparation method thereof

    CN113611889A

  • Preparation method of TiO2-TiNb2O7 composite negative electrode material for lithium ion battery

    CN114792792A

  • CuInNiSnCd high-entropy alloy / carbon fiber composite material and preparation method and application thereof

    CN118287681A